Review of the Flexible Credit Line and Precautionary Credit Line. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
With the creation of the Flexible Credit Line (FCL) and Precautionary Credit Line (PCL), the Fund's GRA toolkit was overhauled to address gaps in the Fund's crisis prevention and resolution toolkit. The innovative and flexible nature of the new instruments was meant to reduce stigma from using Fund resources, underpinning confidence in its users amid stressed market conditions. Yet, there have been a limited number of members with these Using a variety of methodological tools, this review assesses experience with the instruments, arrangements. Using a variety of methodological tools, this review assesses experience with the instruments, reflects on the appropriateness of their design, and recommends refinements to enhance their effectiveness.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet